Investigating the correlation between teachers' instructional communication and students' motivation: A quantitative study - Adara, Reza Anggriyashati; Al Amin, Josi Nur Panuntas (Universitas Negeri Yogyakarta, 2023)
There is an anecdotal evidence that teachers' instruction communication can affect students' communication. Thus, the present study aims to investigate the correlation between teachers' instructional communication and students' motivation. The present study applies a quantitative approach by distributing a set of questionnaires to 52 participants in a senior high school in Bekasi, Indonesia. The findings of the present study indicate a strong correlation between teachers' instruction communication and students' motivation. In addition, the most salient factors of teachers' instructional communication are feedback and organization of instructional units or teachers' ability to deliver the materials. Regarding students' motivation, the majority of the respondents are motivated by integrated regulation. The latter refers to the respondents' ability to internalize their goals. It can be said that feedback and teachers' ability to present learning materials in an engaging manner can help students to see the merits behind their learning process and internalize the goals. The present study also discuss the implications and further studies.